Citizenship and Youth Social Engagement in Canada: Learning Challenges and Possibilities - Ali A. Abdi; Lynette Shultz (Universidade de Lisboa, 2013)
With the general increase in the 'production' of citizenship and global citizenship education scholarship, one might think that we have established a clear and comprehensive understanding of these concepts and their daily implications and possibilities. That may not be the case, and while all claims, contexts and formations of citizenship are important and certainly empower individuals and groups in important ways that directly affect their lives, they do not necessarily explain or actively respond to the qualities of citizenship that people experience, desire or are able to achieve. Our analysis of youth engagement holds that by strengthening the quality of local citizenship, the connections to global citizenship are also affirmed. To discuss and analyse these active youth engagement projects in Canada's public (and to some extent private) spheres, we look into the socio-political formations of three contemporary Canadian youth movements. The first is Lead Now; the second is the Journey of the Nishiyuu and Idle No More and their members; and the third is the student movement that was organized by youth for the adequate funding of higher education in the province of Quebec.